Effect of negative pressure wound therapy applied in the emergency center on postoperative infection rates in patients with orthopedic open wounds - Eriten, Semih; İzci, Vedat; Menekşe, Serdar (The European Research Journal, 2025)
Objectives: This study aimed to evaluate the effect of Negative Pressure Wound Therapy (NPWT) applied in the emergency department on postoperative infection rates in patients with orthopedic open injuries. Methods: This prospective randomized controlled study included 80 patients who presented with orthopedic open injuries. Patients were divided into two groups: NPWT group (n=40) and control group receiving standard wound care (n=40). An average pressure of 125±25 mmHg was applied in the NPWT group. Demographic characteristics, wound characteristics, infection rates, length of hospital stay, and treatment outcomes were evaluated. Results: The infection rate in the NPWT group (7.5%) was significantly lower compared to the control group (25.0%) (P=0.034). The NPWT group showed significantly lower numbers of surgical debridement (1.3±0.6 vs 2.1±0.8, P=0.008), shorter antibiotic use duration (10±3 vs 14±4 days, P=0.003), and shorter hospital stay (8±2 vs 14±3 days, P